2017
DOI: 10.1515/afpuc-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Cation-containing lipid membranes – experiment and md simulations

Abstract: Using small angle neutron diffraction and molecular dynamics simulations we studied the interactions between calcium (Ca 2+ ) or zinc (Zn 2+ ) cations, and oriented gel phase dipalmitoyl-phosphatidylcholine (DPPC) bilayers. For both cations studied at ~1:7 divalent metal ion to lipid molar ratio (Me 2+ :DPPC), bilayer thickness increased. Simulation results helped reveal subtle differences in the effects of the two cations on gel phase membranes. Eur. Pharm. J. 2017, 64 (2): 9-14. Lipid bilayer -metal ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Other calculations have shown that POPC at a calcium concentration of ∼300 mM forms a 1:1 stoichiometry with a 25% probability and clusters with two or three POPC molecules with almost equal probabilities of ∼35–40% ( Melcr et al, 2018 ). This ratio may, however, depend on the ion concentration, and/or it may relate to the concentration-dependent localization of the Ca 2+ ion at certain head groups of the POPC ( Kučerka et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Other calculations have shown that POPC at a calcium concentration of ∼300 mM forms a 1:1 stoichiometry with a 25% probability and clusters with two or three POPC molecules with almost equal probabilities of ∼35–40% ( Melcr et al, 2018 ). This ratio may, however, depend on the ion concentration, and/or it may relate to the concentration-dependent localization of the Ca 2+ ion at certain head groups of the POPC ( Kučerka et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids are ubiquitous molecules that occur naturally in all living organisms as the major components of biomembranes. 1 Various phospholipid classes with different biological functions have been found in nature. Phosphatidylserine (PS) is the major anionic phospholipid class particularly enriched in the inner leaflet of the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%